Between Struggle And Hope (Study Descriptive Reason Student Separated Studying On Faculty Teaching & Knowledge University Education Tribuana Kalabahi) - Saetban, Antonius Abednego; Dony, Petrus Mau Tellu; Tuaty, Desi Anceria (Gema Wiralodra, 2024)
Education will make Indonesian people become intelligent people and can utilize and respond to all opportunities in fulfilling and fighting for life. However, in reality, the economic conditions of the community are certainly different, not all families have adequate economic capacity and are able to fulfill all the needs of family members. One of the effects caused by economic conditions like this is that parents are unable to send their children to a higher level of school even though they are able to finance it at the elementary and middle school levels. It is clear that the economic condition of the family is the biggest supporting factor for the continuation of their children's education to college level, because education also requires large costs. Related to the above intent, researchers want to know more Far about what causes students to drop out of college. This research is aim of finding out the causes of students dropping out of college at Tribuana Kalabahi University, Faculty of Teacher Training and Education. This type of research uses a descriptive method with a qualitative approach . The empirical results of the study show that the causes of students dropping out of college are due to financial constraints and preferring to work, the object of the study and overall the background of families with a lower middle economic level. Most of the respondents' families' livelihoods are farmers with a monthly income of between Rp. 250,000 to Rp. 500,000. Family members as guardians of students who are responsible for the costs of student education also contribute to the cause of students dropping out of college